Blends of bee honey (Apis mellifera L.) and its shelf life due to the proportion of hydroxymethylfurfural (Research, Society and Development, 2020)
We evaluated the effect of the proportions of young and old honeys in the constitution of "blends" used in industrial processing on the quality of honey during storage under conditions of Teresina, PI. We used six samples from new honeys and six old honeys collected in the deposit material from warehouse matter. The experiment was conducted in a completely randomized design in a factorial design with six treatments (proportions) and two times (two months) with six replicates (samples). Were considered as treatments the proportions of young and old honey mixtures, considering the HMF as standard for the preparation of proportion, where: T1 - old honey + new honey (4: 1); T2 - old honey + new honey (3: 1); T3 - old honey + new honey (2: 1); T4 - old honey + new honey (1: 1); T5 - new honey (0: 1); T6 - old honey (1: 0); The largest proportions in the mixtures old honey reduce the quality and shelf life of the honey, whereas HMF as an indicator.